Implementasi Kode Etik Profesi Kepolisian Negara Republik Indonesia Studi Kasus AKBP Achiruddin Hasibuan - Fathoni, Muhammad Nur; Salim, Choirul; Hermawaty, Nety (Siyasah, 2023)
This study aims to complement previous research data to analyze and examine the legal process for violating the POLRI code of ethics carried out by Adjunct Police Chief Commissioner (AKBP) Achiruddin Hasibuan as a basis for carrying out his duties, knowing and analyzing accountability if POLRI commits a violation of the code of ethics, and must responsible for violating the code of ethics, the code of ethics is made based on the professional standards of members, the code of ethics in carrying out their duties. In Regulation of the Head of the State Police of the Republic of Indonesia No. 14 of 2011 concerning the Polri Professional Code of Ethics in Article 1 explains the KEPP explanation, as follows: "POLRI Professional Code of Ethics, hereinafter abbreviated as KEPP, is a norm or rule which constitutes a unified ethical or philosophical basis relating to actions or speech related to things that are obligatory, prohibited, proper or inappropriate to be done by members of the Police in carrying out their duties. and job responsibilities”.